Signet Ring Cell Carcinoma - K.M. Hiwale1 , Avadh Kishor Tyagi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Signet ring cell carcinoma is very rare carcinoma of colon and aggressive subtype of colorectal carcinoma thatis mostly diagnose inadvance stage. 5-year survival rate is very poor as compared to other adenocarcinomaof the colon. First case reported in 1951 but clinical literature on this subtype of adenocarcinoma is verylimited. In this report a 32-year old male presented with SRCC of colon. Our literature review describesthe many factors that contribute to the poor outcome and high recurrence in SRCC of the colon. This studyprove that survival rate is increased by earlydiagnosis and surgical resection. However, the rarity of thiscancer and its propensity for insidious onset and aggressive course prove a challenge to the development ofsuch guidelines.